Evaluación de la gestión institucional y liderazgo educativo en el colegio técnico Jambelí del cantón Santa Rosa, provincia de El Oro periodo 2011-2012, y propuesta alternativa de un modelo de gestión fundamentado en los estándares de calidad y la práctica del buen vivir. - Castillo Herrera, Teresa De Jesús (2015)
In the present research focuses on institutional management and educational leadership Technical College Jambelí, where the faithful compliance with standards of educational quality, which sets the current regime by the Ministry of Education, for this theoretical research was conducted objectively assessed that terminologies and value for understanding the conceptualizations that every professional should know and practice.